1998
DOI: 10.1046/j.1365-2648.1998.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

The practice and perception of intensive care staff using the closed suctioning system

Abstract: Tracheobronchial suctioning using the closed suctioning system (CSS) has physiological benefits for critically ill patients. Despite these benefits, nurses have raised concerns about the CSS. The aims of this study were to identify concerns, count how frequently they occurred and examine the relationship between the concerns and the experience of the operators. Experience was defined as length of time working in an intensive care unit (ICU) and length of time using the CSS. Using a field research approach, six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…15,16 However, this recommendation is based on a misrepresentation of the work of Ackerman and Mick, who actually suggested that routine use of NSI is not supported. 5 Canadian guidelines produced by Brooks et al 17 indicate that there is currently no evidence to support or refute the use of NSI; more recently, Celik and Kanan have reiterated the view that NSI should not be used routinely, 18 suggesting that NSI should be used only when it is needed and when the patient's response to it has been established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 However, this recommendation is based on a misrepresentation of the work of Ackerman and Mick, who actually suggested that routine use of NSI is not supported. 5 Canadian guidelines produced by Brooks et al 17 indicate that there is currently no evidence to support or refute the use of NSI; more recently, Celik and Kanan have reiterated the view that NSI should not be used routinely, 18 suggesting that NSI should be used only when it is needed and when the patient's response to it has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Within the United Kingdom, anecdotal reports have indicated that some hospitals incorporated the complete ban of NSI in their nursing suction protocols, based on reviews reported in nursing literature, and that physiotherapists, despite being autonomous practitioners, are being encouraged to comply. 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…When it is performed through a tight seal closed system suctioning. At this time the intensive care nurses had a clinical impression, supported by a large Canadian survey [66,67], that the closed systems were inefficient in clearing the patients' airways from secretions. This drove the manufacturers of the closed suction systems to recommend use of higher vacuum levels and thicker catheters that could contribute to development of large negative pressure levels in the lungs and/or ventilator.…”
Section: Introduction _______________________________________________mentioning
confidence: 99%
“…exsufflation was not set). This makes direct comparison between the 28 ANDERSON ET AL. 9 also subdivided participants depending on whether they had a scoliosis(n = 4) or not (n = 8) and examined the data separately for each group.…”
Section: Resultsmentioning
confidence: 99%
“…4,16 The technique of suction itself carries inherent risks, including hypoxia, cardiac arrhythmias, pneumothoraces, bronchospasm, and haemodynamic alterations. [24][25][26][27][28] Patients with NM disease are often referred for non-invasive ventilation, with a view to the provision of ventilators for nocturnal domiciliary use to manage hypoventilation. Long-term, nocturnal, non-invasive ventilation is being used with good effect to treat an increasing number of patients with neuromuscular disease, allowing management within the home environment.…”
Section: Discussionmentioning
confidence: 99%